STRATEGI BISNIS USAHA HOME INDUSTRI SPERAI DI KOTA BENGKULU - Jayami Jayami; Rahmat Al Hidayat (STIA Bengkulu, 2023)
Home Bedding Industry is a business unit/company on a small scale which is engaged in certain home linen industry. Usually this business only uses one or two houses as production, administration and marketing centers at the same time. The role of the Home Bedding Industry is very meaningful in empowering the community to have economic independence. Home Industry Bedding which is used as a partner in community service is the home industry for the bedding industry, namely Roza Bed Sheet, Tiara Bed Sheet, Barokah Bed Sheet, Lala Bed Sheet, Putri Bed Sheet. The problem that is often faced in the Home Bedding Industry business is an obstacle in facing business development due to the difficulty of capital, especially during the Covid 19 pandemic. To solve this problem, government support is needed by the community by offering skill institutions (LPK), including trained personnel, product quality, strategic business location, family system, high economic value production, and the use of information technology in marketing their products. The material presented in the mentoring activity is the Home Business Business Strategy for the Bedding Industry. The results of the mentoring show that qualitatively the owner gains additional knowledge, understanding, and insight as well as basic skills about the home bedding industry. From the results of the study, it can be concluded that assistance in the application of the home bedding industry can increase knowledge, understanding and insight for the Home Industry Bed linen business actors.